Hey world, here I am! - Little, Jean, 1932-; Truesdell, Sue ([New York] : HarperCollins, 1989)
A collection of poems and brief vignettes from the perspective of a girl named Kate Bloomfield, reflecting her views on friendship, school, family life, and the world.
Wilson's Children.
Notable/Best Books (A.L.A.).
School Library Journal.
5.1
3-6
Center for the Collaborative Classroom Curriculum.
Keywords: Children's poetry, Canadian -- Juvenile literature; Canadian poetry -- Juvenile literature; Short stories; Canadian poetry; Short stories